Clinical Features and Risk Factors for Mortality in Hospitalized Older Adults with Pneumonia - Nobuhiko Fukuda; Nobuaki Kobayashi; Makoto Masuda; Aya Wakabayashi; Nobuko Kusano; Keisuke Watanabe; Nobuyuki Horita; Yu Hara; Masanori Nishikawa; Takeshi Kaneko (Canadian Respiratory Journal)
Background. Pneumonia is a common disease among the aging population in Japan. Hence, it is important to elucidate the risks related to pneumonia mortality. Since Streptococcus pneumoniae is the most commonly observed pathogen, pneumococcal vaccination is recommended to older adults. Therefore, this study aimed to clarify the clinical features of pneumonia, including the status of pneumococcal vaccination, in hospitalized older adult patients in Japan. Methods. This single-centered retrospective study was conducted by reviewing the medical records of all patients with acute pneumonia at Fujisawa City Hospital in Japan from April 2018 to March 2019. Patients were divided into two groups based on their history of pneumococcal vaccination. The primary endpoint was in-hospital mortality, while the secondary endpoint was risk factors associated with mortality. Results. We included 93 patients with pneumonia in this retrospective study. Although the mortality rate was higher in the vaccinated group (15.8%) than in the unvaccinated group (9.1%), vaccination status was not identified as a significant risk factor for mortality after multivariable logistic regression (odds ratio: 2.71; 95% confidence interval: 0.667–11.02; p=0.16). In addition, the A-DROP score was identified as an independent risk factor (odds ratio: 2.64; 95% confidence interval: 1.22–5.72; p=0.008). Conclusions. Our study suggested that the A-DROP score is a risk factor of mortality for pneumonia in older adults. In addition, pneumococcal vaccination history was related to increased mortality; however, the influence of the vaccination remains unclear because of the small sample size.